2016
DOI: 10.26833/ijeg.285215
|View full text |Cite
|
Sign up to set email alerts
|

The Proposal of the Building Application for More Benefiting From Solar Light

Abstract: ABSTRACT:There is a proverb, that emphasizes the importance of sunlight for human health, which is "Where the sun does not enter the physician enters". It is one of the most important elements to see the sunlight of the buildings for both healthy life and energy saving. The positioning may be desirable to take the advantage of the morning and evening sunlight of the buildings to be constructed in the housing area. Indeed, in 1985 constructed blocks of buildings in Eskisehir Yenikent in public housing projects,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…In order to maximize the sunlight in many parts of Turkey, when the solar azimuth angles of sunrise and sunset at maximum sunrise times are examined, it has been found that the most favorable location for buildings is the position of solar azimuth angle between approximately 150 g and 250 g (Erdem and İnce, 2016), (Figure 2). and minimum at sunset (GB) (Erdem and İnce, 2016) Table 1. Power loss as the amount of shadows falling on the PV panes and the percentage (URL-2).…”
Section: Determination Of Sun Azimuth and Elevation Angles In Shape T...mentioning
confidence: 99%
“…In order to maximize the sunlight in many parts of Turkey, when the solar azimuth angles of sunrise and sunset at maximum sunrise times are examined, it has been found that the most favorable location for buildings is the position of solar azimuth angle between approximately 150 g and 250 g (Erdem and İnce, 2016), (Figure 2). and minimum at sunset (GB) (Erdem and İnce, 2016) Table 1. Power loss as the amount of shadows falling on the PV panes and the percentage (URL-2).…”
Section: Determination Of Sun Azimuth and Elevation Angles In Shape T...mentioning
confidence: 99%
“…The angles α and ε are obtained from the following relations (Allan et al, 1968;Anderson and Mikhail, 1998;Kavanagh, 2000;Kavanagh, 2003;Kavanagh, 2009;İnce and Erdem, 2019). The coordinates of the center of the circle (YO, XO) are derived from the following relations; A→YO = YA + R sin (AO), XO = XA + R cos (AO) (21) B→YO = YB + R sin (BO), XO = XB + R cos (BO) (22) C→YO = YC + R sin (CO), XO = XC + R cos (CO) (23) (Bannister et al, 1992;Bannister et al, 1998, Erdem andİnce, 2016)…”
Section: Calculation Of the Center Coordinates And Radius Of A Circlementioning
confidence: 99%
“…The angles α and ε are obtained from the following relations (Allan et al, 1968;Anderson and Mikhail, 1998;Kavanagh, 2000;Kavanagh, 2003;Kavanagh, 2009;İnce and Erdem, 2019). 23) (Bannister et al, 1992;Bannister et al, 1998, Erdem andİnce, 2016)…”
Section: Calculation Of the Center Coordinates And Radius Of A Circle With Points Marked On Equal Chord Lengthsmentioning
confidence: 99%